Microcontroller exploits - Goodspeed, Travis (No Starch Press, Inc., 2024)
In this advanced guide to hardware hacking, you'll learn how to read the software out of single chip computers, especially when they are configured not to allow the firmware to be extracted. This book documents a very wide variety of microchip hacking techniques; it's not a beginner's first introduction. You'll start off by exploring detailed techniques for hacking real-world chips, such as how the STM32F0 allows for one word to be dumped after every reset. You'll see how the STM32F1's exception handling can slowly leak the firmware out over an hour, and how the Texas Instruments MSP430 firmware can be extracted by a camera flash. For each exploit, you'll learn how to reproduce the results, dumping a chip in your own lab. In the second half of the book, you'll find an encyclopedic survey of vulnerabilities, indexed and cross-referenced for use in practicing hardware security.
Includes bibliographical references and index
Keywords: Penetration testing (Computer security); Computer networks -- Security measures; Hacking; Computer security; Tests d'intrusion; Réseaux d'ordinateurs; Sécurité; Mesures; Piratage informatique; Sécurité informatique